Contributing to the sustainability of cities through education - Flores Lucero, María de Lourdes; Guevara Romero, María Lourdes; Milián Ávila, Guadalupe María (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The accelerated urban growth and the loss of management capacity of governments have contributed to aggravate issues related to natural resources, public space, floods, mobility, demand for public services, etc. In such a situation, it is more than ever necessary to educate students and develop alternative solutions-oriented research. This mission is a commitment that the universities must acquire in their role as a means of transforming both teachers and students way of thinking. In this sense, the objective of this paper is to share our academic experience, particularly in the context of the postgraduate course of the Faculty of Architecture of the Benemérita Universidad Autónoma de Puebla, and to contribute to the reflection on how we can promote, through academic work, more sustainable territorial practices developed in collaboration with civil society and the public sector. One of the most relevant conclusions highlights the need to move from confined research to a more proactive one, aimed at changing the paradigm of the territorial problems’ analysis and response.